Event Management of Kurenah Ibuah Festival in Payakumbuh as a Domestic Tourism Alternative during the Pandemic: A Study of Community Festival - Fresti Yuliza; Dede Pramayoza (International Journal of Applied Sciences in Tourism and Events, 2022)
The world of tourism in West Sumatra, including in Payakumbuh City, experienced a significant degradation during the Covid-19 pandemic. Various tourism events are not held in line with the recommendation for social distancing. This study aims to analyze the Kurenah Ibu Festival activities as an alternative to domestic tourism during the Covid 19 pandemic in West Sumatra. This research was conducted with a qualitative approach adapted to the context of tourism and event research, with content analysis methods that consider several factors from the festival management. The results showed that the management of the Kurenah Ibu Festival as an alternative domestic tourism destination during the Covid 19 pandemic was made possible by several factors, namely: first, choosing a strategic location that is easily accessible by visitors from various directions; second, materials are varied choices that can attract visitors of all ages; three, the application of the CHSE protocol which guarantees health, safety, and security; and four, combining online and offline formats that allow the public from far away to access activities while reducing the number of visitors at the festival. The concept of the Community Festival offered by Kurenah Ibuah Festival, can be a model for the implementation of Tourism Events in the context of the post-pandemic resilience process.